2013
DOI: 10.1136/jech-2013-202576
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent long-standing illness and non-drinking over time, implications for the use of lifetime abstainers as a control group

Abstract: Persistent LSI was associated with remaining a non-drinker across adulthood. Studies comparing the health outcomes of moderate drinkers to lifetime abstainers that do not account for pre-existing poor health may overestimate the better health outcomes from moderate alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 26 publications
(28 reference statements)
3
55
0
Order By: Relevance
“…Alternatively poor health may have an indirect influence on nondrinking being a factor relating to social disadvantage, which has also been found to be related to nondrinking (Jefferis et al., 2007; Ng Fat and Shelton, 2012). These direct and indirect factors may explain why consistent associations between poor health and nondrinking are found in different cohorts, and with older (Newsom et al., 2012; Powers and Young, 2008; Wannamethee and Shaper, 1991) and younger participants (Ng Fat and Shelton, 2012; Ng Fat et al., 2014) including in this study in relation to ex-drinking. Evidence suggests that moderate alcohol consumption and lower cardiovascular disease risk are not causally related (Holmes et al, 2014), countering the conclusions of many J-curve studies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Alternatively poor health may have an indirect influence on nondrinking being a factor relating to social disadvantage, which has also been found to be related to nondrinking (Jefferis et al., 2007; Ng Fat and Shelton, 2012). These direct and indirect factors may explain why consistent associations between poor health and nondrinking are found in different cohorts, and with older (Newsom et al., 2012; Powers and Young, 2008; Wannamethee and Shaper, 1991) and younger participants (Ng Fat and Shelton, 2012; Ng Fat et al., 2014) including in this study in relation to ex-drinking. Evidence suggests that moderate alcohol consumption and lower cardiovascular disease risk are not causally related (Holmes et al, 2014), countering the conclusions of many J-curve studies.…”
Section: Discussionmentioning
confidence: 94%
“…These findings complement previous findings that poor health is associated with nondrinking from an early age (Ng Fat and Shelton, 2012), and persistent poor health with being a persistent nondrinker (Ng Fat et al., 2014), suggesting that there are direct effects of poor health on nondrinking. This study also shows the relationship between a worsening of health and nondrinking is not only a phenomenon that occurs as people age, because the association was present across the life course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, female never drinkers may be less healthy than their male equivalents. Although research concerning the health status of never drinkers is lacking, a recent study analyzing data from the 1958 National Child Development Study found that, of participants to consistently report long-standing illness from the age of 23 years, women were significantly more likely to report being never drinkers at ages 33 and 42 years (41). Such data hint at the possibility that risk factors for type 2 diabetes may be disproportionately distributed between the sexesda problem particularly pronounced for any estimates drawn from poorly adjusted studies.…”
Section: Discussionmentioning
confidence: 99%